2016
DOI: 10.18632/oncotarget.12677
|View full text |Cite
|
Sign up to set email alerts
|

Nivolumab for advanced melanoma: pretreatment prognostic factors and early outcome markers during therapy

Abstract: BackgroundAn anti-programmed cell death protein 1 monoclonal antibody, nivolumab, is one of the most effective drugs for advanced melanoma. Tumor cell-derived or immune cell-derived markers and clinical predictors such as serum lactate dehydrogenase (LDH) and cutaneous adverse events, have already been described as prognostic factors for advanced melanoma treated with nivolumab. We sought to identify further clinical predictors that can be determined in routine clinical practice.MethodsWe retrospectively analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
122
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(142 citation statements)
references
References 37 publications
16
122
3
1
Order By: Relevance
“…Patients whose ECOG performance status exceeded 0 had a 2.2 times higher risk of disease progression, consistent with the study findings by Nakamura et al 30 Intriguingly, patients who were age 73 years or older appeared to show a lower risk of progression compared with patients age 55 years or younger. The neutrophil, platelet, and lymphocyte counts did not appear to differ significantly among the age groups, although the platelet count was significantly higher in patients whose ECOG performance status exceeded 0.…”
Section: Association Of Inflammatory Markers With Disease Progressionsupporting
confidence: 91%
See 1 more Smart Citation
“…Patients whose ECOG performance status exceeded 0 had a 2.2 times higher risk of disease progression, consistent with the study findings by Nakamura et al 30 Intriguingly, patients who were age 73 years or older appeared to show a lower risk of progression compared with patients age 55 years or younger. The neutrophil, platelet, and lymphocyte counts did not appear to differ significantly among the age groups, although the platelet count was significantly higher in patients whose ECOG performance status exceeded 0.…”
Section: Association Of Inflammatory Markers With Disease Progressionsupporting
confidence: 91%
“…Baseline LDH level was found to be associated with overall survival in a separate study. 30 In a Phase 1a trial with the anti-PD-1 ligand antibody atezolizumab in patients with metastatic renal cell carcinoma, the exploration of serum markers showed that low baseline levels of acute serum reactants including α-antitrypsin and fibrinogen and the decrease of ferritin level after treatment were associated with longer overall survival. 31 In our cohort study of a well-described, community-based population, we focused on 3 readily available peripheral blood cell counts and observed that absolute neutrophil count and platelet count were significantly associated with PFS in patients with metastatic melanoma receiving pembrolizumab or nivolumab.…”
Section: Original Research and Contributionsmentioning
confidence: 99%
“…While we advocate careful selection of patients to be treated with anti‐PD‐1 antibodies followed by ipilimumab, specific biomarkers for identifying those mostly likely to benefit are as yet lacking. In the past, our institute reported pretreatment performance status (PS) of 1 or more, maximum tumor diameter of 30 mm or more, elevated lactate dehydrogenase (LDH) and elevated C‐reactive protein (CRP) to be significantly associated with poor OS of patients receiving first‐line nivolumab therapy . To determine whether or not such clinical parameters reflect the prognosis of patients treated with anti‐PD‐1 antibodies followed by ipilimumab, we examined these potential biomarkers in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, we did not detect any correlations between serum 5‐ S ‐CD at baseline and a favorable response to Nivo in 12 cases because median pretreatment serum 5‐ S ‐CD was in fact higher in PR than in PD patients. Serum LD has been proposed as a biomarker in immune‐checkpoint blockade therapy for advanced melanoma, with patients displaying elevated baseline levels being significantly associated with short overall survival compared with those having normal values following treatment with Nivo or other immune‐checkpoint blockade therapies . Therefore, while serum LD should be considered at baseline, 5‐ S ‐CD may be of clinical use for monitoring the early response to immune‐checkpoint blockade therapies in tandem with LD.…”
Section: Discussionmentioning
confidence: 99%